0
$\begingroup$

I'm new to lambda calculus and was wondering if transforming the lambda expression

$v\lambda v.v$

into

$v(\lambda v.)v$

produces the same expression. Could someone help out?

$\endgroup$
1
  • 2
    $\begingroup$ Your second version is not a valid expression in the $\lambda$-calculus. $\lambda$-abstraction is over a term: given a term $v$ its $\lambda$-abstraction is ($\alpha$-equivalent to) $\lambda x . v$. With parentheses, your initial expression $v \lambda v . v$ should be $v (\lambda v . v)$. $\endgroup$ Mar 11, 2013 at 15:38

1 Answer 1

2
$\begingroup$

I'm reposting Benedict Eastbaugh's comment CW:

Your second version is not a valid expression in the $λ$-calculus. $λ$-abstraction is over a term: given a term $v$ its $λ$-abstraction is ($α$-equivalent to) $λx.v$. With parentheses, your initial expression $vλv.v$ should be $v(λv.v)$.

$\endgroup$

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .